L'Éducation en situation de conflit en République centrafricaine : les Espaces Temporaires d'Apprentissage en question - Helena Murseli (Les éditions de la Maison des sciences de l'Homme, 2019)
This article analyses the establishment, the operation and management of Temporary Learning Spaces (TLS) during the transitional government (2014-2016) in Central African Republic, a country which has been facing crises and conflict since its independence in 1960. These Spaces are often set up by governments and the international community in crisis or conflict contexts, when schools are no longer accessible, for different reasons. They aim at allowing children to continue their schooling while benefiting from a protective framework, as well as defending the right to primary education. Drawing on interviews with families, TLS directors and Ministry of National Education officials as well as institutional documentation, this text questions the status of TLS and the respective roles of international actors and the government. How is the TLS institutional anchoring built, despite their controversial status? How to ensure the transition with the formal public education sector, while the crisis is getting longer and the temporary lasts?